Interactions of Aspergillus fumigatus and Stenotrophomonas maltophilia in an in vitro Mixed Biofilm Model: Does the Strain Matter? - Melloul, Elise; Roisin, Lolita; Durieux, Marie-Fleur; Woerther, Paul-Louis; Jenot, Delphine; Risco, Veronica; Guillot, Jacques; Dannaoui, Eric; Decousser, Jean-Winoc; Botterel, Françoise (Frontiers in Microbiology, 2018)
Aspergillus fumigatus (Af) and Stenotrophomonas maltophilia (Sm) are pathogenic microorganisms, which coexist in the respiratory tract of cystic fibrosis patients. We recently developed an in vitro model of mixed biofilm associating Af ATCC 13073-GFP (Af13073) and Sm ATCC 13637 (Sm13637) and described an antibiosis effect. The present study aim was to assess the antibiosis of Sm on Af using different strains and to analyse the potential synergistic virulence of these strains in an in vivo Galleria mellonella model. Methods: The effect of Sm13637 was evaluated on eight Af strains and the effect of nine Sm strains was evaluated on Af13073. The strains originated from clinical cases (human and animal) and from environment. Fungal and bacterial inocula were simultaneously inoculated to initiate mixed biofilm formation. Fungal growth inhibition was analysed by qPCR and CLSM and the fungal cell wall modifications by TEM analysis. The virulence of different Sm strains was assessed in association with Af in G. mellonella larvae. Results: All strains of Af and Sm were able to produce single and mixed biofilms. The antibiosis effect of Sm13637 was similar whatever the Af strain tested. On the other hand, the antibiosis effect of Sm strains was bacterial-fitness and strain dependent. One strain (1/9) originated from animal clinical case was never able to induce an antibiosis, even with high bacterial concentration. In the G. mellonella model, co-inoculation with Sm13637 and Af13073 showed synergism since the mortality was 50% i.e. more than the summed virulence of both. Conclusion: Human clinical strains of Sm yielded in higher antibiosis effect on Af and in a thinner mixed biofilm, probably due to an adaptive effect of these strains. Further research covering Af increased wall thickness in the presence of Sm strains, and its correlation with modified antifungal susceptibility is encouraged in patients with chronic respiratory infections by these 2 microorganisms.